Clinical features, therapy and outcome of patients hospitalized or not for nursing-home acquired pneumonia. Issue 8 (August 2020) - Russo, Alessandro; Picciarella, Alice; Russo, Roberta; Sabetta, Francesco
Abstract: Background: nursing home-acquired pneumonia (NHAP), is among the main causes of hospitalization and mortality of frail elderly patients. Aim of this study was analysis of patients residing in long-term care facilities (LTCF) and developing pneumonia to reach a better knowledge of criteria for hospitalization and outcomes. Materials/methods: this is a prospective, observational study in which patients residing in 3 LTCFs (metropolitan area of Rome, Italy) and developing pneumonia, hospitalized or treated in LTCF, were recruited and followed up from January 2017 to June 2019. Primary endpoint was 30-day mortality, secondary endpoint was analysis of risk factors associated with hospitalization. Results: Overall, 146 episodes of NHAP were enrolled in the study: 57 patients were treated in LTCF, while 89 patients were hospitalized. Overall incidence rates of NHAP varied from 2.6 to 7.5 per 1000 residents. Methicillin-resistant Staphylococcus aureus was the most frequently isolated pathogen (25%), and in 28 (55%) patients was documented a MDR pathogen. For hospitalized patients was reported a higher 30-day mortality (43.8% Vs 7%, p < 0.001). Multivariate analysis showed that severe pneumonia, neoplasm, chronic hepatitis, antibiotic monotherapy, and malnutrition were independent risk factors for hospitalization from LTCF. MDR pathogen, severe pneumonia, COPD, and moderate to severe renal disease were independently associated with death at 30 days. Conclusion: frail elderly patients in LTCF have a high risk of MDR etiology with a higher risk to receive an inadequate antibiotic therapy and a fatal outcome. These results point to the need for increased provision of acute care and strategies in LTCF.